Modelling the control of tsetse and African trypanosomiasis through application of insecticides on cattle in Southeastern Uganda - Kajunguri, Damian (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.